(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In experiments on male Wistar rats during chronic poisoning with organophosphate pesticide antio at a dose of 1/100 LD50, a decrease in immunity parameters was revealed with a concomitant (simultaneous) increase corticosterone levels in the blood, which may be one of the mechanisms for reducing the organizm’s resistance and increasing the number of morbidity in the regions heavy use of pesticides.